Temporal Clinical and Laboratory Response to Interleukin-6 Receptor Blockade With Tocilizumab in 89 Hospitalized Patients With COVID-19 Pneumonia - Daria Fomina; Mar'yana A. Lysenko; Irina P. Beloglazova; Zinaida Yu. Mutovina; Nataliya G. Poteshkina; Inna V. Samsonova; Tat'yana S. Kruglova; Anton A. Chernov; Alexander V. Karaulov (Case Western Reserve University, 2020)
Background: Pandemic COVID-19 pneumonia due to SARS-2 is an important cause of morbidity and mortality. Emerging evidence links poor outcomes to an inflammatory cytokine storm. Methods: We treated 89 hospitalized patients with COVID-19 pneumonia and heightened systemic inflammation (elevated serum C reactive protein and interleukin-6 levels) with an infusion of tocilizumab (TCZ), a human monoclonal IgG1 antibody to the interleukin-6 receptor. Results: Clinical and laboratory evidence of improvement was evident when baseline and 1-2-day post-infusion indices were compared. Among the 72 patients receiving supplemental oxygen without mechanical ventilation, severity of condition on the NEWS2 scale scores fell from 5 to 2 (P<0.001), C reactive protein levels fell from 95 to 14 mg/L (P<0.001), and lymphocyte counts rose from 900 to 1000/uL (P=0.036). Sixty-three of 72 patients were discharged from the hospital, one patient died, and eight patients remained in the hospital at the time of this writing. Among the 17 patients receiving mechanical ventilation, despite a rapid decrease in CRP levels from 89 to 35 mg/L (P=0.014) and early improvements in NEWS2 scores in 10 of 17 patients, 10 patients ultimately died and the other seven remain in the hospital at the time of this writing. Overall, mortality was only seen in patients who had markedly elevated CRP levels (>30 mg/L) and low lymphocyte counts (<1000/uL) before TCZ administration. Conclusions: Inflammation and lymphocytopenia are linked to mortality in COVID-19. Inhibition of IL-6 activity by administration of tocilizumab, an anti-IL-6 receptor antibody, is associated with rapid improvement in both CRP and lymphocyte counts and in clinical indices. Controlled clinical trials are needed to confirm the utility of IL-6 blockade in this setting. Additional interventions will be needed for patients requiring mechanical ventilation.